Correlation between standard and adjusted echocardiographic quantitative methods for evaluating tricuspid regurgitation severity. (4th February 2022) - Tat, E; Hamid, N; Khalique, O; Lehenbauer, K; Sitticharoenchai, P; Nazif, T; Vahl, T; Ng, V; George, I; Cahill, T; Blusztein, D; Mihatov, N; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Current guidelines advocate for a multi-parametric approach to echocardiographic quantitation of tricuspid regurgitation (TR). The primary quantitative measure of TR severity uses the proximal isovelocity surface area (PISA) method to calculate effective regurgitant orifice area (EROA) and regurgitant volume (RegVol). However, EROA-PISA may underestimate TR severity due to low flow and tethering of the tricuspid leaflets. Purpose: The purpose of this study was to compare standard EROA-PISA quantitation of TR to alternative quantitative measures, including quantitative Doppler (EROA-Doppler), flow- and angle-corrected PISA method (EROA-Corrected), and three-dimensional vena contracta area (3D-VCA), in addition to the comparison of calculated RegVol-PISA, RegVol-Doppler, and RegVol-3DVCA. Methods: Patients undergoing both transthoracic (TTE) and transesophageal (TEE) echocardiographic evaluation of TR severity for transcatheter treatment were included in this study. Patients were excluded if they had ≥ moderate aortic regurgitation. TTE measurements of EROA-PISA and RegVol-PISA were performed as per American Society of Echocardiography guidelines. EROA-Doppler was performed by quantifying RegVol-Doppler (diastolic stroke volume using biplane annular area, minus left ventricular outflow stroke volume) and deriving EROA. EROA-Corrected was calculated by adjusting for both aliasing velocity and leaflet angle as per published methods. 3D-VCA was measured on TEE performed within 14 days of TTE. Results: Of 44 consecutive patients, the median age was 80 ± 9 years, 61% were female, and 89% had atrial fibrillation. Most patients (86%) had functional TR, 71% had a EROA-PISA ≥ 0.4 cm2. Table 1 shows the EROA and RegVol results for each method.  EROA-PISA and RegVol-PISA were significantly lower than EROA-Doppler and RegVol-Doppler, as well as 3D-VCA and RegVol-3DVCA (all p < 0.0001). There was no significant difference between EROA-Doppler and 3D-VCA (p = 0.51), and RegVol-Doppler and RegVol-3DVCA (p = 0.66).  EROA-Corrected reduced the absolute difference with EROA-Doppler (51% to 33%, p < 0.0001) and 3D-VCA (52% to 32%, p < 0.0001), but remained statistically lower than EROA-Doppler and 3D-VCA. Although EROA-PISA was strongly correlated to EROA-Doppler (r = 0.75, p < 0.0001) and 3D-VCA (r = 0.68, p < 0.0001), the correlation between EROA-Doppler and 3D-VCA was greatest (r = 0.77, p < 0.0001). Adjusting EROA-PISA for angle and flow demonstrated improved correlation to EROA-Doppler without affecting correlation to 3D-VCA (Figure 1). Conclusion: Our study demonstrated that EROA-PISA significantly underestimates the severity of TR by EROA-Doppler and 3D-VCA. Although PISA correction methods reduced the underestimation, both EROA-Corrected and RegVol-Corrected remained significantly lower. EROA-Doppler and 3D-VCA and the calculated RegVol by each method, were closely correlated and not significantly different.